The rising tide of conservation technology: empowering the fight against poaching and unsustainable wildlife harvest - Lynam, Antony John; Cronin, Drew T.; Wich, Serge A.; Steward, Jordan; Howe, Andrew; Kolla, Namrata; Markovina, Michael; Torrico, Omar; Reyes, Vanesa; Sophalrachana, Kong; Stevens, Xia; Schmidt, Eric; et al. (Frontiers in Ecology and Evolution, 2025)
IntroductionMarket-driven poaching and unsustainable wildlife harvest are significant drivers of population decline for numerous plant and animal species, including high-profile species like Asian and African elephants, wild cats, sharks and rays, and pangolins. This publication reviews the emerging role of conservation technology in combating this trade.Technologies and applicationsWe showcase how innovative technological tools are revolutionizing the detection and disruption of illegal and unsustainable wildlife trade, with a focus on those available to frontline staff working to prevent poaching and trafficking from source sites. We consider a diverse array of deployed technologies ranging from open-source software platforms, AI, and mobile apps to cutting-edge hardware, including camera traps, acoustic sensors, and remote sensing tools.Case studiesTo demonstrate the complex threats posed by IUWT to wildlife and the consequent need for tailored solutions, we present two case studies, one terrestrial and one marine, showcasing the importance of appropriate suites of technology tools for conservation implementation.DiscussionTechnology has potential to empower rangers, park staff, wildlife and fisheries inspectors, customs officials, police, and conservation practitioners with unprecedented capabilities to monitor threatened wildlife, detect illegal activities, gather evidence, and support law enforcement interventions.